2015
DOI: 10.1111/obr.12247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bariatric surgery on physical functioning in obese adults

Abstract: Obesity is associated with a profound impairment in the ability to perform the basic physical activities required for everyday function. This impacts on quality of life and contributes to disability. Bariatric surgery leads to weight loss and metabolic improvements in severe obesity; however, less is known about its effect on physical functioning. This narrative review summarizes current evidence on the effect of bariatric surgery on this outcome with a consideration of the mechanisms involved. Nine longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
4
44
0
1
Order By: Relevance
“…The findings from this study reinforce shorter-term results from studies that have reported significant improvements in SF-36 bodily pain and physical function scores, 2932 WOMAC scores, 29,33,34 walking capacity (as measured by the LDCW or the 6-minute walk test), 30,31,35,36 resting heart rate, 35,36 or other measures of pain and function 1012 in the first 3 to 12 months following RYGB or LAGB. Few studies have reported on pain and function from longer-term follow-up of these procedures.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The findings from this study reinforce shorter-term results from studies that have reported significant improvements in SF-36 bodily pain and physical function scores, 2932 WOMAC scores, 29,33,34 walking capacity (as measured by the LDCW or the 6-minute walk test), 30,31,35,36 resting heart rate, 35,36 or other measures of pain and function 1012 in the first 3 to 12 months following RYGB or LAGB. Few studies have reported on pain and function from longer-term follow-up of these procedures.…”
Section: Discussionsupporting
confidence: 82%
“…8,9 Although evidence of improvements in pain and physical function following bariatric surgery is increasing, the variability and durability of improvement have not been well described—with most studies limited by small sample size and follow-up of 1 year or less or by the study of obsolete surgical procedures. 1012 …”
mentioning
confidence: 99%
“…These functional abilities are often limited in obese individuals, hence exercise training that improves physical function is important 5 . The ISWT is a valid field based test of functional capacity and aerobic fitness as it strongly relates to VO 2 max 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is increasing evidence of weight regain in patients after bariatric surgery 2,3 , generally occurring between 12 and 24 months post-operatively 2,4 . Weight regain increases the risk of physical function decline which negatively affects an individual's ability to undertake activities of daily living 5 . Weight regain also increases the likelihood of obesity related co-morbidities returning 6 , hence the importance of recommendations on diet and physical activity after bariatric surgery to prevent weight regain 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in the group which had more than 18% weight reduction, VO 2 peak (mL/min) was significantly reduced after surgery. Thus, improvement of physical functioning in patients after bariatric surgery is more a mechanical phenomenon of consequential weight loss than an absolute improvement of cardiopulmonary and muscle function [35]. Therefore, the risk of poor cardiorespiratory and muscle function may persist postsurgically in patients despite their weight loss.…”
Section: Discussionmentioning
confidence: 99%